Ultrabroadband light absorbing Fe/polymer flexible metamaterial for soft opto-mechanical devices. (June 2021) - Güell-Grau, Pau; Pi, Francesc; Villa, Rosa; Nogués, Josep; Alvarez, Mar; Sepúlveda, Borja
Highlights: A new ultrabroadband absorber material (84% average in the 300–18000 nm range) based on nanostructured Fe and PDMS layer has been developed. The ultrabroadband absorption results from the combination of the optical properties of highly-damped plasmonic materials with the infrared absorption of thin polymer films. The material shows excellent photothermal efficiency and a large thermal-expansion mismatch between the layers, leading to large mechanical deflections. We exploit these properties to develop soft light actuated devices, like an artificial iris that self-regulates the transmitted light power. Abstract: Ultrabroadband light absorbers are attracting increasing interest for applications in energy harvesting, photodetection, self-regulated devices or soft robotics. However, current absorbers show detrimental insufficient absorption spectral range, or light angle and polarization dependence. Here we show that the unexplored optical properties of highly-damped plasmonic materials combined with the infrared absorption of thin polymer films enable developing ultrabroadband light-absorbing soft metamaterials. The developed metamaterial, composed of a nanostructured Fe layer mechanically coupled to a thin polydimethylsiloxane (PDMS) film, shows unprecedented ultrabroadband and angle-independent optical absorption (averaging 84% within 300–18000 nm). The excellent photothermal efficiency and large thermal-expansion mismatch of the metamaterial is efficiently transformed into large mechanical deflections, which we exploit to show an artificial iris that self-regulates the transmitted light power from the ultraviolet to the long-wave infrared, an untethered light-controlled mechanical gripper and a light-triggered electrical switch. Graphical abstract: Image, graphical abstract